Sustainable Entrepreneurship and Circularity: Stakeholder Collaboration in Textile SMEs in Indonesia - Istiyani, Ambar; Surya Putra, Yanuar; Dian Pramesti, Novita (Research Synergy Foundation, 2024)
The textile industry is a significant contributor to environmental degradation, leading to an increasing emphasis on sustainable entrepreneurship and circular supply chains. This qualitative case study examines the experiences of textile-based SMEs in Indonesia who use shredded fabric from larger textile industries to create new fashion products. The urgency of this study lies in understanding the challenges faced by small- and medium-sized enterprises (SMEs) in textile-based circular supply chains, particularly in their collaboration with stakeholders. The in-depth interviews with five SME owners, two consumers, a supplier, a government official, and a CSO activist uncovered several critical challenges, including limited availability and access to shredded-fabric and inconsistent quality and quantity of the raw material, transforming the shredded-fabric into finished fashion products, reaching SMEs’ target market and promoting their products effectively, and the management of small leftover fabric pieces from production, referred to as “tatal.” The study proposes the following strategies to address the challenges: foster trust and transparency with suppliers, reactivate the joint business cooperative, work with government agencies and policymakers to establish customized support and regulatory structures, collaborate with government agencies and academic institutions, expand the market for tatal waste beyond the arts, and partner with the Department of the Environment to manage tatal waste. The findings contribute to the academic literature on sustainable entrepreneurship and provide practical insights for SMEs, policymakers, and industry stakeholders to enhance the circularity of textile supply chains.